(untitled) (Canadian Medical Education Journal, 2020)
Implication: Here we report a simulation session carried out with pre-clerkship medical students during their gastroenterology block. We used endoscopy simulator to cement the clinical and anatomic implications of endoscopy and to build interest in gastroenterology. Students thought the session was helpful for their interest and understanding. Endoscopy simulation provided for pre-clinical students could help to bolster high-level understanding of gastroenterology as well as understanding of clinical and procedural aspects of the specialty.